Dual Time F-18 FDG PET/CT Imaging in the Diagnosis of Renal Cell Cancer - Karyagar, Savas; Koc, Zehra Pinar; Karyagar, Sevda S.; Ozulker, Tamer; Topal, Cevat; Karaguzel, Ersagun; Balci, Tansel Ansal (Bentham Science Publ Ltd, 2014)
Background: There are conflicting results in estimation of primary renal tumors by F-18 FDG PET/CT in the literature. Aim of this study is to evaluate diagnostic efficiency of F-18 FDG PET/CT and dual time imaging in the diagnosis of renal cell cancer. Methods: Dual time F-18 FDG PET/CT examinations of 17 patients (55.2 +/- 9.9 years old; 7 F, 10 M) with prediagnosis of renal cell cancer were retrospectively evaluated. All of the patients underwent operation and histopathological results were compared with PET/CT results. In order to compare numerical variables Kolmogorov-Simirnov, Mann Whitney U and Paired samples T tests were performed in SPSS version 15.0 and p<0.05 considered statistically significant. Results: Among 17 patients 15 patients were confirmed to have renal cell carcinoma, 2 patients had benign pathologies (oncocytoma, metanephritic adenoma). According to the early phase analysis, the sensitivity, specificity, accuracy, positive and negative predictive values of PET/CT regarding diagnosis of primary tumor were 20%, 100%, 29%, 100% and 14%, respectively. Additionally the difference between SUVmax values in the early and the late phase was not statistically significant (p>0.05). Conclusion: Since only the positive predictive value of PET/CT is sufficiently high and the sensitivity is very low, diagnosis of renal tumors by F-18 FDG PET/CT is not an accurate method. In addition, dual-phase imaging in the diagnosis of renal cell cancer has no benefit.
Keywords: Dual phase imaging; F-18 FDG; PET/CT; renal cell cancer; renal tumor; SUV